Association between Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis in subgingival plaque and clinical parameters, in Argentine patients with aggressive periodontitis. (May 2015) - Sánchez, Gabriel A.; Acquier, Andrea B.; De Couto, Alejandra; Busch, Lucila; Mendez, Carlos F.
Abstract: Background: Aggregatibacter actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg) have been associated with aggressive (AgP) and chronic periodontitis. Objective: The aim of this study was to evaluate the levels of Aa and Pg in gingival crevicular fluid (GCF) of patients with AgP and its relation with clinical parameters. Design: Sixteen females and fourteen males with clinical diagnosis of AgP aged 17–23 years and their match's controls, were included in this study. Clinical recording concerning probing pocket depth, clinical attachment level, plaque index and gingival bleeding index were performed at baseline, 30 and 60 days after baseline. After clinical examination GCF samples were analyzed for Aa and Pg with a real-time polymerase chain reaction technique. Patients group was treated with a combined of mechanical and oral antibiotic therapy (doxycycline 100 mg/day, during 21 days). A multivariate analysis was used to determine the relationship between Aa and Pg counts with clinical parameters. Results: GCF from all subjects was positive for Aa and PG. In controls Pg concentration was higher than Aa (Pg: 42, 420 ± 3, 034 copies/ml; Aa: 66.6 ± 5.4 copies/ml p < 0.001) while in patients both microbes showed the same concentration (Aa: 559, 878 ± 39, 698 Pg: 572, 321 ± 58, 752). A significant and positive correlation was observed between counts of Aa and Pg (R square: 0.7965, p < 0.0001). Female showed more counts/ml. Aa might be closely associated with clinical parameters while Pg did not. At 30 and 60 days Aa counts in patients were similar to controls while Pg counts were equal to baseline. However, in spite of Pg presence a clinical improvement was observed in all patients. Conclusions: In our population the presence of Aa may be associated with AgP while Pg may be in GCF as an opportunistic pathogen which might caused disease when the ecological balance was favorable. Highlights: Aa and Pg were determined in patients with aggressive periodontitis and controls. Association of Aa and Pg with periodontal clinical parameters was evaluated. Both microbes were detected in control and patients groups. Pg and Aa showed similar counts in patients but only Aa was related to the disease. Mechanical and doxycyclin therapy decreased Aa and improved periodontal disease.